A host–guest ATP responsive strategy for intracellular delivery of phosphopeptides. Issue 41 (16th April 2020) - Han, Bei-Bei; Pan, Yu-Chen; Li, Yan-Mei; Guo, Dong-Sheng; Chen, Yong-Xiang
Abstract : A new host–guest ATP responsive strategy for efficient intracellular delivery of phosphopeptides using a pegylated arginine clustered calix[5]arene nanocarrier system. Abstract : We developed a host–guest ATP responsive strategy for efficient intracellular delivery of phosphopeptides, employing a pegylated arginine clustered calix[5]arene nanocarrier system that has great capability of recognizing the phosphate moieties on peptides and penetrating the cell membrane.